2015
DOI: 10.21608/bvmj.2015.32657
|View full text |Cite
|
Sign up to set email alerts
|

Impact of industrial wastewater on water and fish quality of Nile River in Kafr El-Zayat, Egypt

Abstract: City, which potentially affect and deteriorate its quality. To study the impact of these effluents on aquatic environment of the Rosetta branch, a total of 108 water samples and 36 fish samples were collected during the spring and autumn 2010 from 9 different regions along the branch at Kafr El-Zayat industrial area. Chemical analyses of water samples showed seasonal variation of pH, Pb, Cd, and NH3 values. Cu concentrations in the water were below the maximum permissible limit, however, Pb, Cd, Hg, P, NH3, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
4
6
0
Order By: Relevance
“…Seasonal variations of copper concentrations may be due to the fluctuation of agricultural drainage water and sewage effluents discharged into this canal. Similar observations were recorded by Daifullah et al (2003) and didn't match with those obtained by Moustafa et al (2010) and Alawy et al (2015) whom recorded the highest value of copper concentration during spring and the lowest value during autumn. Manganese: The maximal value of manganese in the water was recorded at Kalleeb Ebiar Village during spring (178.30 ± 24.30 µg/L) and the lowest (11.33 ± 2.31 µg/L) during autumn at Hesset Abar Village.…”
Section: Heavy Metals In the Watersupporting
confidence: 76%
“…Seasonal variations of copper concentrations may be due to the fluctuation of agricultural drainage water and sewage effluents discharged into this canal. Similar observations were recorded by Daifullah et al (2003) and didn't match with those obtained by Moustafa et al (2010) and Alawy et al (2015) whom recorded the highest value of copper concentration during spring and the lowest value during autumn. Manganese: The maximal value of manganese in the water was recorded at Kalleeb Ebiar Village during spring (178.30 ± 24.30 µg/L) and the lowest (11.33 ± 2.31 µg/L) during autumn at Hesset Abar Village.…”
Section: Heavy Metals In the Watersupporting
confidence: 76%
“…Thus, to reduce the excessive free radical production, in the present study, Nile tilapia were exposed for a period of four weeks to copper or zinc in the presence of duckweed Lemna minor. The concentrations used in the mesocosm water (Cu: 0.004 mg/L and 0.02 mg/L; Zn: 05 mg/L and 1.5 mg/L) match those estimated in polluted areas in Egypt [48]. However, at the proteomic level, after high Cu exposure and both low and high Zn exposure, the magnitude of hepatic activity of GST and GPx decreased, as has been reported in the liver of Nile tilapia [15,16,46].…”
Section: Discussionsupporting
confidence: 56%
“…The eighth and ninth groups were exposed to water with the same concentrations of zinc as in the previous groups plus one layer of duckweed covering the water surface. The applied doses of copper and zinc were based on the permissible concentrations in natural water [47] and the estimated levels in polluted areas in Egypt [48]. At the end of the four-week, fish were euthanized and dissected.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The contamination of water bodies in the Egyptian Nile Delta region including Lake Manzala is exposed to release of enormous amounts of domestic sewage as well as agricultural and industrial effluents [41]. The bacterial load of fish is a reflection of the water status in which they were caught and therefore, fish can acquire pathogenic microorganisms from the natural aquatic environment [42]. It has been reported that all the fish samples collected from Lake Manzala were contaminated on surface and internally with exceptionally high amounts of bacteria at gill and intestine confirming that lake fish is profoundly polluted and dangerous for human health [43].…”
Section: Discussionmentioning
confidence: 99%